Microstructures and mechanical properties of an a-C:N film as the interlayer and the outmost layer of a DLC-deposited Ti bio-alloy. (August 2017) - Chou, Chau-Chang; Lin, Jyun-Sin; Wu, Rudder
Abstract: An amorphous carbon nitride (a-C: N) interlayer was deposited by radio frequency plasma enhanced chemical vapor deposition (rf PECVD) using a mixture of methane (CH4 ) and nitrogen gases to improve the adhesion between diamond-like carbon (DLC) films and Ti6Al4V substrate. The DLC film was deposited by the same technique using a mixture of CH4 and hydrogen precursors. Another sample, deposited with an additional a-C:N outmost layer on the mentioned DLC coating, was also proposed to study the characteristics of the interface between a-C:N and DLC films. The structures and film thicknesses of the DLC and a-C:N coatings were investigated by Raman spectroscopy, X-ray photoelectron spectroscopy, and scanning electron microscopy. The mechanical properties were evaluated by indentation and scratch tests. The results showed that depositing an a-C:N film on Ti alloy and on DLC film by a continuous rf PECVD procedure can modify the coated materials and improve adhesion. However, the additional a-C:N film deposited on the DLC/a-C:N coating was not suitable for the softer Ti6Al4V substrate due to its brittle nature when subjected to concentrated loading. To summarize, depositing an a-C:N film as the interlayer between DLC coating and Ti biomedical alloy is a promising alternative to the amorphous Si interlayer which is widely used in medical applications.